When Parents Fail to Mind the Child: Lower Mentalizing in Parents Who Maltreat Their Children - Rosso, Anna Maria (Frontiers in Psychology, 2022)
Mentalization is considered an essential ability for social cognition as well as a crucial competency in parenting to further the development of internal structures that are decisive for self organization and affect regulation in children. Yet, few empirical studies have investigated whether, and to what extent, parents who maltreat their children poorly mentalize. The aim of this research was to study the mentalization ability in a group of parents who maltreated their children and had been referred by the Courts for Child Custody and Parenting Plan Evaluation (group 1), and in a comparison, nonclinical group of parents (group 2). Adult Attachment Interview, rated in terms of both the Berkeley AAI System and the Reflective Functioning Scale was administered. Group 1 had severely impaired reflective functioning (RF) in 83.3% of cases, whilst impaired RF was found in only 12.5% of group 2 parents. For the most part, parents in group 1 showed Negative Reflective Functioning, systematically resisting taking a reflective stance, and the parents who most severely maltreated their children showed distorted and/or self-serving passages associated with a particular type of dismissing pattern of attachment (DS2) based on the derogation of attachment. The frequent occurrence of derogation in these parents likely explains how much the devaluation of relationships and attachment needs, presumably acquired during childhood with defensive purposes and in order to exclude the pain and perception of emotional weakness from awareness, hinders the capacity to care for children in the full respect of their needs.